OPTIMIZATION OF TURBULIZATOR SPRAYER PARAMETERS BY MATHEMATICAL PLANNING METHOD OF EXPERIMENTS - Doniyorovich, Khusniddin Irisov; Ashirbekovich, Ivadulla Ashirbekov; Mengqobilovich, Sobir Sherqobilov; Ergashovich, Fayzulla Begimkulov (International Journal of Psychosocial Rehabilitation, 2020)
The article highlights the tasks of the stable advancement of diversified and cluster farms in the Republic of Uzbekistan, existing problems in the cultivation of agricultural crops that are planned to be resolved in recent years, in addition to the development of high-quality crops, it has been acknowledged particularly that one of the major potential problems is to improve the technological efficiency and technical- economic performance of chemical defoliation agents, particularly in cotton. In this research, improving the technical efficiency of liquid chemicals (defoliants) used in the process of cotton defoliation, analysis of technologies and technical means developed by the world’s leading scientists in this field, although the defoliation process is one of the important factors in improving cotton yield and fiber quality, the working hypothesis by the authors on the formation of highly dispersed droplets has not yet been sufficiently developed in this area, scope, essence, design scheme, technological process of operation of the proposed promising vortex- turbilizator, the theoretical aspects of the formation of high-dispersion droplets, methods, individual dimensions of droplets per 1 cm2 of the object of study, their distribution, total number of drops, drop density scanner, computer and a multi-factor regression equation representing the detection process in a specially designed software system called "DepositScan" and the process of generating the highly dispersed droplets proposed using a multifactor experiment, optimal values of the main factors of the turbilizator, according to which the working fluid pressure to the reduction of the median-mass diameters of the formed droplets, the annual technical and economic efficiency of the experimental spraying unit equipped with a new sprayer are determined by the fact that the width of the annular holes in the sprayers has a greater impact on the increase in working fluid consumption.